2010
DOI: 10.1071/wr10052
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous mating in feral pigs (Sus scrofa) from Texas, USA

Abstract: Context Feral pigs represent a significant threat to agriculture and ecosystems and are disease reservoirs for pathogens affecting humans, livestock and other wildlife. Information on the behavioural ecology of feral pigs might increase the efficiency and effectiveness of management strategies. Aims We assessed the frequency of promiscuous mating in relation to oestrous synchrony in feral pigs from southern Texas, USA, an agroecosystem with a widespread and well established population of feral pigs. An associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The mating system of this species has been originally described as polygynous (Mauget 1980;Dardaillon 1984), which is consistent with the sexual dimorphism displayed by the species (Ralls 1977). Interestingly, with the rise of molecular genetic techniques, a growing literature has shown that multiple paternity occurs (Delgado et al 2008;Poteaux et al 2009) and may be common in some populations of wild pigs (Delgado-Acevedo et al 2010;Costa et al 2012). A positive effect of multiple paternity on litter size has even been highlighted in the domestic pig (Sus scrofa domesticus), which is the domestic counterpart of the wild boar.…”
supporting
confidence: 55%
“…The mating system of this species has been originally described as polygynous (Mauget 1980;Dardaillon 1984), which is consistent with the sexual dimorphism displayed by the species (Ralls 1977). Interestingly, with the rise of molecular genetic techniques, a growing literature has shown that multiple paternity occurs (Delgado et al 2008;Poteaux et al 2009) and may be common in some populations of wild pigs (Delgado-Acevedo et al 2010;Costa et al 2012). A positive effect of multiple paternity on litter size has even been highlighted in the domestic pig (Sus scrofa domesticus), which is the domestic counterpart of the wild boar.…”
supporting
confidence: 55%
“…Young males leave their family packs when they are approximately one year old and form their own packs outside of the family groups. The mating system is commonly described as polygynous (Fernández-Llario et al 1999), some authors, however, describe it as polygynandrous or promiscuous (Pérez-González et al 2014) in view of evidence of multiple paternity within litters (Delgado-Acevedo et al 2011).…”
mentioning
confidence: 99%
“…The outbreeding avoidance based on different parental genomes might produce problems of genetic diversity conservation and, hence might reduce the fitness of individuals (e. g. Acevedo‐Whitehouse et al ., ). This trend might be counteracted with other processes that favour the genetic diversity maintenance such as seasonal partner switch, litter production, multiple paternity, sex‐biased dispersal and mate competition (Karl, ; Delgado‐Acevedo et al ., ; Pérez‐González et al ., ).…”
Section: Discussionmentioning
confidence: 99%